An unusual intracardiac electrogram showing cause for false electrical discharge from an ICD. (2nd August 2013) - Mohammed, Ishaq; Ratib, Karim; Creamer, John
Abstract : We describe a rare case of inappropriate implantable cardioverter defibrillator (ICD) therapy due to false sensing of electromechanical interference from diathermy as 'ventricular fibrillation (VF)'. This occurred during surgical removal of sternal wires under general anaesthesia. Postsurgical interrogation of ICD revealed the intracardiac electrogram showing the mechanical interference sensed as 'VF' by ICD and subsequent shock delivery.